PEMANFAATAN SATWA LIAR SEBAGAI SUMBER PROTEIN HEWAHI OLEH ETNIK TEHIT KNASAIMOS DI DISTRIK SAIFI KABUPATEN SORONG SELATAN PROVINSI PAPUA BARAT DAYA - Rudi Aprianto Maturbongs; arlan kapisa; meliza sartje worabai (Universitas Muhammadiyah Sorong, 2023)
The purpose of this research is to uncover the types of wild animals that serve as a source of animal protein for the Tehit Knasaimos ethnic group in Saifi District, South Sorong Regency, Southwest Papua Province. The descriptive method with survey techniques was used for this study. Data analysis was conducted using the UVs, ICF, and FL formulas. It was revealed that the utilization of wild animals as a source of animal protein is intended for self-consumption (subsistence), sale, traditional ceremonies, and religious events. The hunted wild animal species by the Tehit Knasaimos ethnic group amounted to 19 species, consisting of mammals (7 species), birds (5 species), reptiles (2 species), fish (1 species), and crustaceans (3 species). Wild boar (Sus scrofa) and dusky pademelon (Thylogale brunii) are the most extensively utilized wild animal species in the Tehit Knasaimos community (UVs = 0.22 - 0.61). The FL values in the four utilization categories by the Tehit Knasaimos ethnic group reveal that the most preferred wild animal species are wild boar (52.9% - 61.1%) and dusky pademelon (58.8% - 61.1%). The greater melampitta (Talegala jobiensis) is most preferred for ceremonial purposes (52.9%). The informants' information homogeneity is high to very high for self-consumption/subsistence utilization (ICF = 0.88 - 0.95), traditional purposes (ICF = 0.80 - 0.87), sale (ICF = 0.73 - 0.86), and religious purposes (ICF = 0.79 - 0.84). The long-beaked echidna (Zaglossus bruijnii) is an endemic New Guinea species that is protected due to its declining population in the wild.